Visi dan Ambisi di Kalangan Mahasiswa STT GPI Papua: Antara Panggilan Pelayanan dan Pencapaian Pribadi - Ananda D. Batsira (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2025)
Students at the Theological Seminary (Sekolah Tinggi Teologi, STT) of GPI Papua bear a dual identity, not only as prospective church ministers but also as individuals with personal aspirations concerning academic achievement, social mobility, and future professional paths. The tension between vocational calling and personal ambition constitutes an existential challenge that influences the construction of motivation, spirituality, and life orientation among theology students. This study aims to analyze the dialectical dynamics between these two dimensions and to examine how local Papuan cultural values shape students’ interpretations and efforts to harmonize them. The research problem stems from a lack of integrative theological understanding of personal ambition within the context of vocational ministry. Employing a qualitative approach with a phenomenological design, data were collected through in-depth interviews and analyzed thematically to identify meaning structures, internal conflicts, and integration strategies employed by the students. The findings reveal that personal ambition is not necessarily antithetical to the calling of ministry; rather, it can serve as a constructive force when interpreted through a reflective spirituality grounded in contextual theology. Ambitions guided by Christian values can enhance ministerial capacity and foster authentic personal growth, whereas unmanaged ambition tends to lead to spiritual fragmentation. This study contributes a scientific model of integration between spiritual, personal, and cultural dimensions within theological formation. It recommends a reformulation of curriculum and spiritual formation strategies that are contextual, dialogical, and oriented toward the development of a holistic and culturally relevant vocational identity.